Green practices to implement green hotel concept at Grand Hotel des Alpes, France - I Kadek Petit Arsenal; Ni Nyoman Sri Astuti; I Nyoman Rajin Aryana; Raden Roro Rieta Anggraheni (Politeknik Negeri Bali, 2022)
This research aimed to analyze the implementation the implementation of Green practices and Green hotel concept in Grand Hotel des Alpes, France. It is a descriptive statistic research where questionnaires were distributef to 14 employees in the hotel. The data were collected through observation, document study, literature review, and questionnaires. The result of the study implies that there are aspects that are implemented very appropriately, namely aspects of land use, aspects of energy efficiency, aspects of environmental management, and aspects of operational management. The aspects that are implemented accordingly are aspects of water conservation, aspects of the use of space materials, and aspects of Environmentally Friendly Hotel Operations. The Green practices has been applied appropriately to support the Green hotel concept implementation at Grand Hotel des Alpes, Chamonix, France. Grand Hotel des Alpes has implemented Green practices and Green hotel in line with the Green Hotel Association concept.